2005
DOI: 10.1210/en.2005-0016
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Murine Uterine Genes Regulated in a Ligand-Dependent Manner by the Progesterone Receptor

Abstract: Progesterone (P4) acting through its cognate receptor, the progesterone receptor (PR), plays an important role in uterine physiology. The PR knockout (PRKO) mouse has demonstrated the importance of the P4-PR axis in the regulation of uterine function. To define the molecular pathways regulated by P4-PR in the mouse uterus, Affymetrix MG U74Av2 oligonucleotide arrays were used to identify alterations in gene expression after acute and chronic P4 treatments. PRKO and wild-type mice were ovariectomized and then t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
126
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(135 citation statements)
references
References 47 publications
8
126
1
Order By: Relevance
“…Microarray analysis was performed by Affymetrix murine genome U74Av2 mouse oligonucleotide arrays (Affymetrix) as previously described (30). All experiments were repeated 3 times.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microarray analysis was performed by Affymetrix murine genome U74Av2 mouse oligonucleotide arrays (Affymetrix) as previously described (30). All experiments were repeated 3 times.…”
Section: Methodsmentioning
confidence: 99%
“…The identification of P4-regulated pathways in the uterus is thus crucial for understanding the impairments that underlie disruption of steroid hormone control of uterine cell proliferation and differentiation. In previous studies, we have identified P4-regulated genes using microarray analysis on P4-treated PRKO uteri (30). We have identified Mig-6 as a target of SRC-1 and PR in the uterus.…”
Section: Downregulation Of Mig-6 In Human Endometrialmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, perturbations in the maternal decidual response inevitably lead to pregnancy complications, most prevalent of which is miscarriage 2 . SGK1, a serine/threonine protein kinase homologous to AKT, is rapidly induced in response to a rise in progesterone levels in both human and mouse endometrium, first in epithelial cells and then in the decidualizing stroma [13][14][15] . SGK1 is a key regulator of sodium transport in mammalian epithelia, most prominently through its ability to directly activate epithelial sodium channel (ENaC) and to enhance their expression by inhibiting the ubiquitin ligase NEDD4-2 5,6 .…”
mentioning
confidence: 99%
“…Several investigators reported the genes regulated by progesterone in the uterus with cDNA microarray [8,9]. Recently, gene targeting was used to create knockout mice for PR (PR knockout mouse: PRKO mouse) [10,11].…”
mentioning
confidence: 99%